Algunas reflexiones sobre el enfoque de género y la representación de la sexualidad - Figueroa Perea, Juan Guillermo (El Colegio de México A.C., 1997)
In this paper, the author presents some empirical references concerning the ways individuals experience sexuality and reproduction, specifically the interpretations of men and women interviewed in different demographic surveys. Based on this, some insights into the meaning of the differences showed by the surveys are suggested. The question to be discussed is whether those differences are natural or a result of social constructions about the meaning of being a man and being a woman within the context of sexuality and reproduction.The gender perspective is used in order to structure an alternative interpretation of how demography has viewed reproduction, contraception and sexual practices. The article conclude with a certain aspects of reflection on women's autonomy as one possibility of rethinking the meaning of being a man or being a woman, as well as the relationships between both, by applying a gender perspective.